Patient benefit from seamless implant monitoring - Wallbrück, Karsten (Zdravniški vestnik, 2005)
Background. Patients with electrostimulation devices visit the hospital regularly for follow-up. The workload of out-patient departments is ever increasing, but a less frequent check-up is unwanted, as it could impair reliability and effectiveness of the therapy. A system of remote patient monitoring might improve this situation by enabling identification of patientswho benefit from a shortened time for corrective action after any undesired event. A completely automatic system for patient remote monitoring has been introduced (BIOTRONIK Home Monitoring, HM). Daily patient and device data are display on an internet site which allows authorized persons to followthe parameters trends. Several clinical studies are presently being conducted to investigate the benefit of HM in pacemaker and implantable cardioverter/defibrillator therapy. Preliminary results show the systems ability to individualize implant therapy for the patients and the physicians benefits. Previous studies in heart failure (HF) therapy have shown that hospital readmission rates, hospitalisation duration and also mortality can bereduced by patient monitoring programs. A recently started study investigating HM in heart failure therapy aims to define a HF-indicator that predicts a worsening of the patients status leading to hospitalisation. With such an indicator, the responsible physician could be alerted and the patient can be called in. Although several issues connected to Home Monitoring remain to be solved, the time has come for a more flexible patient management. The incorporation of modern information technology into cardiovascular implants offers a way to solve the conflict between limited resources and high quality medical therapy for an aging population.
Keywords: Atrial Fibrillation; Cardiac Pacing, Artificial; Defibrilatorji, vsadek; Defibrillators, Implantable; Heart Failure, Congestive; Hospitalizacija; Hospitalization; Preddvorna fibrilacija; Srce, odpoved kongestivna; Srčno vzpodbujanje, umetno